2020
DOI: 10.1177/1934578x20902558
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps militarisExerts Antitumor Effect on Carboplatin-Resistant Ovarian Cancer via Activation of ATF3/TP53 Signaling In Vitro and In Vivo

Abstract: This study aimed to investigate the effect of Cordyceps militaris extract on the proliferation and apoptosis of carboplatin- resistant SKOV-3 and determine the underlying mechanisms for overcoming carboplatin resistance in human ovarian cancer. We cultured the carboplatin-resistant SKOV-3 cells in vitro until the exponential growth phase and then treated with different concentrations of C. militaris for 24, 48, and 72 hours. We performed cell proliferation assay, cell morphological change assessment using tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…FDY003 and its active ingredients possess anti-OC properties. The growth-arrest and pro-apoptotic effects of Cm in OC cells are mediated by the pharmacological regulation of TNF-α, TNF receptor 1, NF-κB, activating transcription factor 3 (ATF3), caspase, poly ADP-ribose polymerase (PARP)-1, B-cell lymphoma (Bcl)-2, and Bcl-2-associated X protein (Bax) pathways 111,112 . Cordycepin targets Dickkopf-related protein 1 (Dkk1), autophagy-related protein 8 (ATG8), beclin, microtubule-associated protein 1A/1B-light chain 3 (LC3), β-catenin, matrix metalloproteinase (MMP), transforming growth factor (TGF)-β, vimentin, peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1α, E-cadherin, estrogen receptor (ER)-α, mitochondrial, CC chemokine ligand 5 (CCL5), Akt, NF-κB, the long form of cellular FLICE-inhibitory protein (c-FLIP L ), and caspase signaling of OC cells; these pharmacological effects inhibit the survival, self-renewal potential, viability, EMT, metastasis, therapeutic resistance, migration, and invasion of OC cells 113-116 .…”
Section: Resultsmentioning
confidence: 99%
“…FDY003 and its active ingredients possess anti-OC properties. The growth-arrest and pro-apoptotic effects of Cm in OC cells are mediated by the pharmacological regulation of TNF-α, TNF receptor 1, NF-κB, activating transcription factor 3 (ATF3), caspase, poly ADP-ribose polymerase (PARP)-1, B-cell lymphoma (Bcl)-2, and Bcl-2-associated X protein (Bax) pathways 111,112 . Cordycepin targets Dickkopf-related protein 1 (Dkk1), autophagy-related protein 8 (ATG8), beclin, microtubule-associated protein 1A/1B-light chain 3 (LC3), β-catenin, matrix metalloproteinase (MMP), transforming growth factor (TGF)-β, vimentin, peroxisome proliferator-activated receptor-gamma coactivator (PGC)-1α, E-cadherin, estrogen receptor (ER)-α, mitochondrial, CC chemokine ligand 5 (CCL5), Akt, NF-κB, the long form of cellular FLICE-inhibitory protein (c-FLIP L ), and caspase signaling of OC cells; these pharmacological effects inhibit the survival, self-renewal potential, viability, EMT, metastasis, therapeutic resistance, migration, and invasion of OC cells 113-116 .…”
Section: Resultsmentioning
confidence: 99%
“…Quadrupole Time-of-Flight mass spectrometry was performed according to the procedures described in our previous study. 20 Briefly, liquid chromatography (LC) separation was performed with an Acquity I-Class UPLC (Waters Corp.) with an Acquity UPLC BEH C18 column (1.7 μm, 2.1 × 100 mm). A SYNAPT G2-Si system (Waters Corp.) with the MSe acquisition technique was used for MS detection.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, for about two decades, many researchers have been focused on the medicinal properties of the metabolites of C. militaris (Matsuzawa, Furuya, & Hirotani, 1983; Mouri et al, 1991; Yuan, Zhang, Fan, & Yang, 2008; Zhang, Wen, Duan, Zhang, & Ma, 2019). Furthermore, many studies have confirmed that C. militaris has many striking bioactivities such as immunomodulatory (Liu et al., 2016), antitumor (Jo, Jang, Yang, Jang, & Park, 2020), anti‐aging(Ji, Jia, Li, Wang, & Cai, 2009), antioxidant (Chen, Wu, & Huang, 2013), anti‐inflammatory (Smiderle et al., 2014), anti‐influenza effects (Ohta et al, 2007), antifibrotic (Nan, Park, Yang, Song, Ko, & Sohn, 2001) and so on. However, the popularity and high demand for C. sinensis and C. militaris has led to the scarcity of them, leading to their classification as protected endangered species (Cunningham & Long, 2018).…”
Section: Introductionmentioning
confidence: 95%